2021
DOI: 10.47191/ijmra/v4-i7-01
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Principal's Leadership Style and Work Motivation on Teacher Performance at SMK Negeri 2 Tebing Tinggi

Abstract: This research uses a quantitative approach, where the symptoms will be measured using numbers. The results of this study, the multiple linear regression equation Y = 15,676 + 0.681X1 - 0.080X2. This means that the principal's leadership style variables and motivation have a significant relationship with teacher performance at SMK Negeri 2 Tebing Tinggi. The coefficient determinant of R² is 0.502 or 50.2%. This means that the Principal leadership style variable (X1) and motivation (X2) can explain the teacher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, commitment is an intervening variable in the influence of school-based management on teacher performance ( Haitami et al, 2022 ). The influence of the principal on teachers is indeed profound ( Albuni, 2022 ; Chomariah et al, 2022 ; Nizar, 2021 ; Nurhasyim et al, 2021 ; Timang et al, 2021 ), The principal’s capability to manage schools has a bearing on teacher performance ( Fatkurinah, 2020 ; Suhardi, 2019 ). In the final analysis, teachers who demonstrate high commitment are likely to exhibit high performance, as indicated in a study involving 93 teachers, which revealed the impact of teacher compensation and commitment on teacher performance ( Setiawan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, commitment is an intervening variable in the influence of school-based management on teacher performance ( Haitami et al, 2022 ). The influence of the principal on teachers is indeed profound ( Albuni, 2022 ; Chomariah et al, 2022 ; Nizar, 2021 ; Nurhasyim et al, 2021 ; Timang et al, 2021 ), The principal’s capability to manage schools has a bearing on teacher performance ( Fatkurinah, 2020 ; Suhardi, 2019 ). In the final analysis, teachers who demonstrate high commitment are likely to exhibit high performance, as indicated in a study involving 93 teachers, which revealed the impact of teacher compensation and commitment on teacher performance ( Setiawan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%